Peningkatan Kemampuan Menulis Artikel Berita dan Pemanfaatan Istilah Bahasa Inggris dalam Headline dan Artikel Berita - Englishtina, Inti; Marwinda, Kristin; Mega Mahardhika, Steffie; Al Ihyak Dieni, Novita (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2024)
This study aims to determine the effectiveness of news article writing training focused on using English terms in headlines and articles. Participants were students from NU 3 Mualimin High School, Weleri District, Kendal Regency, with varying expertise levels. The training involved intensive workshops on news article structure, appropriate writing styles, and correct use of English terms. Results are expected to provide insights into the impact of training on improving article quality, particularly in English term usage. Evaluation included qualitative analysis of articles before and after training, considering changes in writing style, information clarity, and English term usage skills. The study also discusses challenges faced by authors and presents recommendations for further improvement, aiming to enhance writing skills in the context of globalization and the influence of English in mass media